Analisis Pewarna Sintesis Rhodamin B Dan Logam Berat Pada Pewarna Bibir Yang Beredar Di Kota Tasikmalaya - Sonya Nurizki Vikandari; Mochamad Herdi Nurzaman; Euis Asrinawangsih; Salsabila Adlina; Susanti Susanti (Mathematics Education Study Program, 2025)
Rhodamine B synthetic dye and heavy metal Lead (Pb) are two substances that are harmful to health and are often misused by the cosmetics industry including lip color. The use of Rhodamine B synthetic dyes is strictly prohibited in cosmetics, while for heavy metals Pb has a limit requirement for contamination in cosmetics, which is £ 20 ppm. The purpose of this study was to determine the presence of synthetic dye Rhodamine B and heavy metal Pb in lip color circulating in Tasikmalaya City. The research method used was quantitative analysis using atomic absorption spectrophotometry (AAS) and UV-Vis spectrophotometry. The results obtained from this study, all samples were identified as containing synthetic dye Rhodamine B and identified as containing heavy metal Pb in samples A, C, D, E as much as £ 0.001 ppm and in sample B as much as 0.196 ppm